Epidemiological aspects of gastro-intestinal parasites in buffalo in Bhola, Bangladesh - BISWAS, HIRANMOY; DEY, ANITA RANI; BEGUM, NURJAHAN; DAS, PRIYA MOHAN (The Indian Journal of Animal Sciences, 2014)
A survey was conducted to investigate the prevalence of parasitic infections of buffalo in Bhola district from September 2011 to August 2012. Out of 497 examined buffaloes 419 (84.90%) were found infected with gastro- intestinal parasites. Thirteen (13) species of gastro-intestinal parasites were identified, of them 4 species were trematodes (Fasciola gigantica (25.40%), Paramphistomum cervi (41.40%), Schistosoma indicum (5.80%), Schistosoma spindale (2.40%)); 6 species of nematodes (Haemonchus contortus (9.70%), Toxocara vitulorum (3.0%), Trichuris ovis (3.0%), Strongyles (0.80%), Strongyloides papillosus (2.0%), Capillaria sp. (0.40%)), 1 species of cestode (Moniezia expansa (0.60%)), and 2 species protozoa (Eimeria zuernii (7.0%) and Buxtonella sulcata (37.40%)). In this study, prevalence of gastro-intestinal parasites in relation to age, sex, seasonal dynamics and nutritional status of the animal were studied. Significantly higher prevalence was observed in summer (84.30%) followed by rainy (83.62%) and winter (81.16%). Females (87.53%) were 1.20 times more susceptible to gastro- intestinal parasitic infection than males (84.37%). In age group, significantly higher prevalence was in adult (88.81%) followed by young (83.45%) and calves (68.05%). In nutritional status group, significantly higher rate of infection was in poor conditioned buffalo (96.61%) than that in medium body conditioned buffalo (75.51%). Egg per gram/ cyst per gram/oocyst per gram of feces was also determined and ranged from 100–1,600. The present study has not emphasized on the losses due to parasitic infection. So it is necessary to assess the economic losses due to parasitic infections and to find out effective control strategies against it.